Brief Report: Vaginal Viral Shedding With Undetectable Plasma HIV Viral Load in Pregnant Women Receiving 2 Different Antiretroviral Regimens. (1st December 2021) - Frenkel, Lisa M.; Morrison, R. Leavitt; Fuller, Trevon L.; Gouvêa, Maria Isabel; Benamor Teixeira, Maria de Lourdes; Coombs, Robert W.; Shapiro, David E.; Mirochnick, Mark; Hennessey, Roslyn; Whitson, Kyle; Chakhtoura, Nahida; João, Esaú C.
Abstract : Background: Pregnant women using antiretrovirals (ARVs) may have persistent vaginal viral shedding, which could be associated with sexual and perinatal HIV transmission. However, there are scant data on vaginal viral load (VVL) in pregnant women with undetectable plasma viral load (PVL). Methods: This study was a post hoc analysis of an open-label randomized trial to evaluate the virologic response of 2 ART regimens. The participants were ART-naive women living with HIV initiating ART regimens between 20 and 36 weeks of pregnancy recruited at 19 clinical sites in 6 countries. Participants were randomized to receive 400 mg of raltegravir 2 times a day or 600 mg of efavirenz 4 times a day in addition to 150 mg of lamivudine and 300 mg of zidovudine 2 times a day. VVL and PVL tests were performed at every study visit. The primary outcome measures were HIV-1 PVL and VVL at maternal study week 4 and rates of perinatal HIV transmission. Results: A total of 408 were enrolled, of whom 323 had VVL samples 4 weeks after enrollment and were included in this analysis. Among women with undetectable/nonquantifiable PVL during ART, the overall rate of quantifiable VVL at week 4 was 2.54% (7/275). Of the 275 with nonquantifiable PVL, 99.1% (115/116) and 96.2% (153/159) had nonquantifiable VVL in the efavirenz and raltegravir arms, respectively. None of the 7 women with quantifiable VVL at the week 4 study visit transmitted HIV to their infants. Conclusions: Detectable VVL in pregnant women with undetectable/nonquantifiable PVL while receiving ART was rare and not associated with perinatal HIV transmission. Abstract : Supplemental Digital Content is Available in the Text.